التحريف الزمني للسرد في قصص (زكريا تامر) - كريم, ظاهر لطيف; حسن, ئەڤین رمزى (Sulaimani Journal for Humanities, 2001)
Zakaria Tamer's stories have been expressing pain, ivory and displease, these expresions haven't been used externally but they embodied, within new technics and methods, want the writer tried to express of all the bitterness accumulated in his depths, following all the compelling phenomenoas committed against the humanity. Therefor, we considered " the time atteration of naration " were the writer tried to include the past and present history vocabularies for graceful purposes, which allows him the freedom for free play of time in away that doesn't effect on events, not only in terms of quiddity and excistance, but also in terms of order and formation.